Assessing IRAK4 Functions in ABC DLBCL by IRAK4 Kinase Inhibition and Protein Degradation. Issue 12 (17th December 2020) - Zhang, Jing; Fu, Liqiang; Shen, Bin; Liu, Yingtao; Wang, Wenqian; Cai, Xin; Kong, Linglong; Yan, Yilin; Meng, Ryan; Zhang, Zhuming; Chen, Ying-Nan P.; Liu, Qian; et al.
Summary: The interleukin-1 receptor-activated kinase 4 (IRAK4) belongs to the IRAK family of serine/threonine kinases and plays a central role in the innate immune response. However, the function of IRAK4 in tumor growth and progression remains elusive. Here we sought to determine the enzymatic and scaffolding functions of IRAK4 in activated B-cell-like diffuse large B cell lymphoma (ABC DLBCL). We chose a highly selective IRAK4 kinase inhibitor to probe the biological effects of kinase inhibition and developed a series of IRAK4 degraders to evaluate the effects of protein degradation in ABC DLBCL cells. Interestingly, the results demonstrated that neither IRAK4 kinase inhibition nor protein degradation led to cell death or growth inhibition, suggesting a redundant role for IRAK4 in ABC DLBCL cell survival. IRAK4 degraders characterized in this study provide useful tools for understanding IRAK4 protein scaffolding function, which was previously unachievable using pharmacological perturbation. Graphical Abstract: Highlights: Development of a series of highly selective IRAK4 degraders Deconvolution of IRAK4 kinase and scaffolding functions in ABC DLBCL Evaluation of the consequences of IRAK4 degradation on key signaling pathways Abstract : Zhang and Fu et al. developed a series of IRAK4 degraders designed from an IRAK4-selective kinase inhibitor to deconvolute IRAK4 kinase and scaffolding functions in ABC DLBCL cells. Interestingly, neither kinase inhibition nor protein degradation affected cell proliferation or apoptosis, suggesting a redundant role of IRAK4 in ABC DLBCL.